2021
DOI: 10.1667/rade-20-00241.1
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Simulation of SARS-CoV-2 Radiation-Induced Inactivation for Vaccine Development

Abstract: Immunization with an inactivated virus is one of the strategies currently being tested towards developing a SARS-CoV-2 vaccine. One of the methods used to inactivate viruses is exposure to high doses of ionizing radiation to damage their nucleic acids. While gamma (c) rays effectively induce lesions in the RNA, envelope proteins are also highly damaged in the process. This in turn may alter their antigenic properties, affecting their capacity to induce an adaptive immune response able to confer effective prote… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 59 publications
2
25
0
1
Order By: Relevance
“…The survival curves indicate that high-LET radiations require a larger dose to inactivate SARS-CoV-2. This is consistent with the results of the previous study by Francis et al (2021) , however, the data are not quantitatively the same. This may be due to differences in geometry of SARS-CoV-2.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The survival curves indicate that high-LET radiations require a larger dose to inactivate SARS-CoV-2. This is consistent with the results of the previous study by Francis et al (2021) , however, the data are not quantitatively the same. This may be due to differences in geometry of SARS-CoV-2.…”
Section: Resultssupporting
confidence: 89%
“…Therefore, the number of damaged spikes normalized per single RNA damage is interesting. We are looking for a radiation field that causes the least number of damaged spikes per single RNA break as suggested by ( Durante et al, 2020 ; Francis et al, 2021 ) for the first time. This ratio is represented in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An MC simulation of ionizing radiation damage to the SARS-CoV-2 found that γ-rays produced significant S protein damage but much less membrane damage. 199 Thus, the γ-rays were proposed as a new effective tool to develop inactivated vaccines. A metropolis MC sampling process was applied to simulate a pharmacokinetic model of the human immunodeficiency virus (HIV) drug darunavir against SARS-CoV-2.…”
Section: Methods and Approachesmentioning
confidence: 99%
“…Simulasi adalah suatu metode yang digunakan untuk mengeksekusi perilaku dan model dalam perangkat lunak [3]. Model simulasi biasanya memperhitungkan keadaan sistem yang ditangkap melalui nilainilai variabel yang telah ditetapkan [4]. Simulasi sering digunakan dalam mempelajari atau menganalisis perilaku kerja dari suatu sistem atau proses oleh manajemen dalam menyelesaikan pekerjaannya [5].…”
Section: Pendahuluanunclassified